Dinámica estacional De micorrizas arbusculares y hongos septaDos enDofíticos oscuros en asociación con raíces De Solanum elaeagnifolium cav. - Osuna Avila, Pedro (2021)
Background: The silver nightshade is associated for endophytic dark septate fungi (HOS) and arbuscular mycorrhiza (MA) in tropical ecosystems, but their colonization has not been studied in each phenological stage along the seasons of the year in an arid urban zone. Question: Which fungal structures occurs simultaneously and are related with each growth stage of the silver nightshade? Species study: Solanum elaeagnifolium Study site and years of study: Juarez City, Chihuahua, Mexico, 2014 Method: The roots were treated with a dual stained of trypan blue and sudan IV to distinguish the mycorrhizal colonization structures of both fungi in the silver nightshade life cycle during the four seasons of the year. The mean of fungal structures of root length with their total colonization per millimeter was evaluated. Results: The simultaneous colonization of the fungi was in all the seasons which morphological diversity was related to the host phenology. The mean of the total colonization for their structure of both fungi (HOS: 64.2 ± 7.2 y HMA: 31.5 ± 3.2 per mm of root length) represented the major significance of root association in spring. The hyaline hyphae as the active structures of the HOS and the arbuscules of the HMA were consistent in the seasons of the year. Conclusions: This is the first report to show the mycorrhizal colonization ‘Arum’ type and describe the co-occurrence of the HMA and the HOS in relation with the silver nightshade phenology per seasonal year in an urban area of the Chihuahuan Desert.